Phi (?) and psi (?) angles involved in malarial peptide bonds determine sterile protective immunity (2012)
Modified HABP (mHABP) regions interacting with HLA-DR?1 molecules have a more restricted conformation and/or sequence than other mHABPs which do not fit perfectly into their peptide binding regions (PBR) and do not induce an acceptable immune response due to the critical role of their ? and ? torsion angles. These angle’s critical role was determined in such highly immunogenic, protection-inducing response against experimental malaria using the conformers (mHABPs) obtained by 1H-NMR and superimposed into HLA-DR?1?-like Aotus monkey molecules; their phi (?) and psi (?) angles were measured and the H-bond formation between these molecules was evaluated. The aforementioned mHABP propensity to assume a regular conformation similar to a left-handed polyproline type II helix (PPIIL) led to suggesting that favouring these conformations according to their amino acid sequence would lead to high antibody titre production and sterile protective immunity induction against malaria, thereby adding new principles or rules for vaccine development, malaria being one of them.